2023
DOI: 10.1109/tnnls.2022.3149091
|View full text |Cite
|
Sign up to set email alerts
|

Resource-Aware Time Series Imaging Classification for Wireless Link Layer Anomalies

Abstract: The number of end devices that use the last-mile wireless connectivity is dramatically increasing with the rise of smart infrastructures and requires reliable functioning to support smooth and efficient business processes. To efficiently manage such massive wireless networks, more advanced and accurate network monitoring and malfunction detection solutions are required. In this article, we perform a first-time analysis of image-based representation techniques for wireless anomaly detection using recurrence plo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 36 publications
(42 reference statements)
0
8
0
Order By: Relevance
“…Recently, the RP has been widely used in deep learning to transform a univariate time-series data into a 2-D image for CNN. It has been shown that the RP brings performance improvement compared to using the raw time series data in several applications [39], [40].…”
Section: Recurrence Plotmentioning
confidence: 99%
“…Recently, the RP has been widely used in deep learning to transform a univariate time-series data into a 2-D image for CNN. It has been shown that the RP brings performance improvement compared to using the raw time series data in several applications [39], [40].…”
Section: Recurrence Plotmentioning
confidence: 99%
“…The proposed classification model, that will serve as the backbone as pe Figure 1 for our TL model, is presented in Figure 3. Considering potential resource restrictions of BEMS the backbone model was developed according to the design consideration guidelines presented in [42], making the model resource-aware. During our iteration process we considered:…”
Section: A Proposed Modelmentioning
confidence: 99%
“…Link-related anomalies caused by faulty hardware degradation or software related imperfections were observed by [10]. To automatically detect such faults, they proposed shallow ML-based techniques that were later proven to perform worse compared to DL-based methods [11]. However, these DL-based methods exhibited high computational complexity making them less suitable to run on constrained devices typical for DITEN setups.…”
Section: Introductionmentioning
confidence: 99%